Assessment of the Psychophysiological State of Female Operators Under Simulated Microgravity - Lebedeva, Svetlana; Shved, Dmitry; Savinkina, Alexandra (Frontiers in Physiology, 2022)
The article describes methods of non-verbal speech characteristics analysis used to determine psychophysiological state of female subjects under simulated microgravity conditions (“dry” immersion, DI), as well as the results of the study. A number of indicators of the acute period of adaptation to microgravity conditions was described. The acute adaptation period in female subjects began earlier (evening of the first day of DI) and ended faster than in male ones in previous studies (2nd day of DI). This was indicated by a decrease in the level of state anxiety (STAI, p<0,05) and depression-dejection (POMS, p<0,05), as well as a decrease in pitch (p<0,05) and voice intensity (p<0,05). In addition, women, apparently, used the "freeze" coping strategy - the proportion of neutral facial expressions on the most intense days of the experiment was at maximum. The subjects in this experiment assessed their feelings and emotions better, giving more accurate answers in self-assessment questionnaires, but at the same time tried to look and sound as calm and confident as possible, controlling their expressions. Same trends in the subjects’ cognitive performance were identified as in similar experimental conditions earlier: the subjects’ psychophysiological excitement corresponded to better performance in sensorimotor tasks. The difference was in the speed of mathematical computation: women in the present study performed the computation faster on the same days when they made fewer pauses in speech, while in men in previous experiments this relationship was inverse.